The Effect of Emotional Freedom Technique (EFT) to Anxiety Level of Pre-Percutaneous Coronary Intervention (Nursing Care Journal, 2022)
Abstract: Coronary Heart Disease (CHD) is a heart function disorder due to a lack of heart muscle blood due to narrowing of the coronary arteries. One of the invasive measures that the usual way to treat CHD is Percutaneous Coronary Intervention (PCI). The problem that often arises in pre-PCI patients is anxiety. The anxiety must be treated, because it can disrupt the patient's hemodynamic condition becomes unstable. This study aims to determine the effect of EFT on the anxiety of patients who will be treated undergoing PCI. This research design uses a quasi-experimental with the approach of one group pre-post test with control group. Number of samples in the study. These are 24 respondents who are divided into 2 groups, so that 12 respondents become intervention group and 12 respondents became the control group with a sampling technique sample using purposive sampling. The statistical test used is Paired T-Test to compare the pre-test and post-test scores in each group and Independent T-Test was used to compare the difference in anxiety between groups intervention and control groups. The results showed that EFT administration had significant effect on the level of anxiety of patients who will undergo PCI with difference in score 2.833 and p-value 0.05 (0.0001). The recommendation of this research is that EFT can be one of the additional interventions to overcome the anxiety of pre PCI patients.